2017
DOI: 10.1556/168.2017.18.2.8
|View full text |Cite
|
Sign up to set email alerts
|

A test of naturalness indicator values to evaluate success in grassland restoration

Abstract: How should the somewhat vague term of restoration success be measured? This is a critical question rooted in European law, where in fact the creation of proper replacement habitats is a prerequisite for permitting projects that trigger a loss of species or habitats. Previous studies have used indices that relied on a comparison to reference sites, for example the number of a predefined pool of target species or compositional similarity. However, since restoration sites have rarely the same biotic and abiotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Despite some criticism, bio-indication in general and naturalness indicators in particular have solid theoretical bases and obvious practical advantages (Diekmann, 2003). Earlier analyses have shown that mean naturalness values are able to indicate habitat naturalness/degradation (Erdős et al, 2017;Sengl et al, 2016Sengl et al, , 2017. Here, we calculated the unweighted mean value for each plot, as it is more efficient in site indication than cover-weighted approaches (Tölgyesi et al, 2014).…”
Section: Data Analysesmentioning
confidence: 99%
“…Despite some criticism, bio-indication in general and naturalness indicators in particular have solid theoretical bases and obvious practical advantages (Diekmann, 2003). Earlier analyses have shown that mean naturalness values are able to indicate habitat naturalness/degradation (Erdős et al, 2017;Sengl et al, 2016Sengl et al, , 2017. Here, we calculated the unweighted mean value for each plot, as it is more efficient in site indication than cover-weighted approaches (Tölgyesi et al, 2014).…”
Section: Data Analysesmentioning
confidence: 99%
“…Additionally, influencing factors such as the distance to the mined sites, vegetation zone, geology, weather, encroachment, and disturbances should be considered. However, the traditional comparison to reference sites for similar composition and/or condition [37,38] is not enough; reclaimed sites rarely have similar biotic and abiotic conditions [21], and it may lack or degrade due to unavoidable disturbances (natural/anthropogenic), or fluctuate over time.…”
Section: Initial/reference State (I0)mentioning
confidence: 99%
“…Adequate incorporation of these gaps demands active involvement of multidisciplinary stakeholders characterizing attributes of the new ecosystem and integrating both the ecological integrity and human well-being in a single framework [20,21]. It is interdisciplinary, cutting across traditional subject boundaries, and predicated on the hypothesis that ought to create an enabling avenue for diverse ecosystems and land-use systems with its sustainable and cultural values [4,14,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of naturalness reflects the degree of degradation of the natural state of the ecosystem and consists in comparing the current and natural states. Assessing naturalness or habitat degradation is one of the most important challenges of conservation biology (Erdős et al, 2017(Erdős et al, , 2018 because it helps in the designation of protected areas (Moravčík et al, 2010), supports management activities (Goncharenko, Yatsenko, 2020;Lykholat et al, 2021), and facilitates effective monitoring of restoration projects (Sengl et al, 2017;Yao et al, 2019;Côté et al, 2021). The naturalness is inversely related to degradation: the more degraded the habitat, the lower its naturalness (Winter, 2012).…”
Section: Introductionmentioning
confidence: 99%